Aggressive Colonization Screening and Infection Control Measures in Containment of NDM-5 Carbapenemase-Producing CRE. (October 2020) - Kamal-Ahmed, Ishrat; Tyner, Kate; Fitzgerald, Teresa; Moulton-Meissner, Heather Adele; McAllister, Gillian; Halpin, Alison; Ashraf, Muhammad Salman; Safranek, Tom; Walters, Maroya; Tierney, Maureen
Abstract : Background: In April 2019, Nebraska Public Health Laboratory identified an NDM-producing Enterobacter cloacae from a urine sample from a rehabilitation inpatient who had recently received care in a specialized unit (unit A) of an acute-care hospital (ACH-A). After additional infections occurred at ACH-A, we conducted a public health investigation to contain spread. Methods: A case was defined as isolation of NDM-producing carbapenem-resistant Enterobacteriaceae (CRE) from a patient with history of admission to ACH-A in 2019. We conducted clinical culture surveillance, and we offered colonization screening for carbapenemase-producing organisms to all patients admitted to unit A since February 2019. We assessed healthcare facility infection control practices in ACH-A and epidemiologically linked facilities by visits from the ICAP (Infection Control Assessment and Promotion) Program. The recent medical histories of case patients were reviewed. Isolates were evaluated by whole-genome sequencing (WGS). Results: Through June 2019, 7 cases were identified from 6 case patients: 4 from clinical cultures and 3 from 258 colonization screens including 1 prior unit A patient detected as an outpatient (Fig. 1). Organisms isolated were Klebsiella pneumoniae (n = 5), E. cloacae (n = 1), and Citrobacter freundii (n = 1); 1 patient had both NDM-producing K. pneumoniae and C. freundii . Also, 5 case patients had overlapping stays in unit A during February–May 2019 (Fig. 2); common exposures in unit A included rooms in close proximity, inhabiting the same room at different times and shared caregivers. One case-patient was not admitted to unit A but shared caregivers, equipment, and devices (including a colonoscope) with other case patients while admitted to other ACH-A units. No case patients reported travel outside the United States. Screening at epidemiologically linked facilities and clinical culture surveillance showed no evidence of transmission beyond ACH-A. Infection control assessments at ACH-A revealed deficiencies in hand hygiene, contact precautions adherence, and incomplete cleaning of shared equipment within and used to transport to/from a treatment room in unit A. Following implementation of recommended infection control interventions, no further cases were identified. Finally, 5 K. pneumoniae of ST-273 were related by WGS including carriage of NDM-5 and IncX3 plasmid supporting transmission of this strain. Further analysis is required to relate IncX3 plasmid carriage and potential transmission to other organisms and sequence types identified in this study. Conclusions: We identified a multiorganism outbreak of NDM-5–producing CRE in an ACH specialty care unit. Transmission was controlled through improved infection control practices and extensive colonization screening to identify asymptomatic case-patients. Multiple species with NDM-5 were identified, highlighting the potential role of genotype-based surveillance. Funding: None Disclosures: Muhammad Salman Ashraf reports that he is the principal investigator for a study funded by an investigator-initiated research grant.